Introduction: Evolutionary Theory and Its Applications to New World Settlement Studies - González José, Rolando (2011)
The first descriptions of Americans were not framed on scientific grounds or according to a specific research program. Rather, they were mere beliefs and conjectures stated by fifteenth and sixteenth century Spanish explorers who joined expeditions to still unknown lands and inhabited the colonies. Many of them, like Gonzalo Fernández de Oviedo, José de Acosta, Luis de Gomara, Bartolomé de las Casas, and Bernardino de Sahagún, were fascinated with the question of the origins of Native Americans. Thus, since the epochs of Columbus and Moctezuma, curiosity about Native American origins has not only been of scientific interest. It should be viewed, to a certain extent, as one more among the many inquiries naturally posed by two cultures making contact.